ALASAN PENDERITA DEPRESI MEMILIH PENGOBATAN AKUPUNKTUR - Chantika Mahadini; Mayang Wulandari (Jurnal Kesehatan Hesti Wira Sakti, 2022)
Introduction The purpose of this study was to qualitatively describe the reasons people with depression choose acupuncture treatment. Methode Method uses descriptive qualitative research. The sampling technique used is a purposive sample with semi-structured interview data collection techniques. Data analysis used descriptive qualitative analysis method. Results Showed that out of 10 people with depression, 5 patients said the reason for choosing acupuncture treatment was because acupuncture treatment did not cause side effects and could relieve depression without taking tranquilizers. Conclusion Can be concluded that acupuncture treatment was chosen because there are no side effects, can relax, relieve insomnia and can slowly decide the consumption of sedatives. Keywords: Acupuncture,Depression, Treatment.